John Peter Peterson or Jemubhai Popatlal Patel?: â€œThe Uncannyâ€ Doubleness and â€œCrackingâ€ of Identity in Kiran Desaiâ€™s Inheritance of Loss - Jayaraman, National University of Singapore, Uma (Asiatic: IIUM Journal of English Language and Literature, 2011)
The condition of diaspora is born of a twin process of displacement from familiar systems of knowledge and the emergence of other spaces in a transnational sphere of communication. While these spaces may hold promises of liberation for the individual, they can also become spaces of entrapment because these are in-between spaces constructed on ideologies unique to them. Â Â Revisiting some theories of diaspora that define these in-between as spaces of empowerment, this article aims to address the complications that attend the birth of the diasporic spaces in order to explore whether such spaces can be non-negotiable spaces of empowerment. It can be established that claims of empowerment are a result of a strategically imagined identity and such identity is easily challenged by the fluidity of these spaces which makes home â€œunheimlich.â€ Â Â This article examines the portrayal of Jemubhai Patel in Kiran Desai’s Inheritance of Loss (2006) through his experiences in colonial, postcolonial and postnational spaces of India in order to identify what makes India a diasporic space for him, and how he needs to repeatedly strategise performance of his perceived identity to survive in these spaces. However, all attempts at survival are challenged by the fluidity of these spaces, which in turn, make the home space â€œunheimlichâ€ and, the experience of living in these spaces, â€œuncanny.â€